Impact of Citral and Phloretin, Alone and in Combination, on Major Virulence Traits of Streptococcus pyogenes - Mohd Adil (Molecules, 2019)
Streptococcus pyogenes is well documented as a multi-virulent and exclusively human pathogen. The LuxS-based signaling in these bacteria has a crucial role in causing several infections through pathways that are pathogenic. This study evaluated the individual and synergistic effects of citral and phloretin against S. pyogenes in relation to major virulence traits. The in vitro synergy of citral and phloretin was evaluated by the checkerboard method. The fractional inhibitory concentration (FIC) values were calculated to determine the interactions between the inhibitors. The bacteria’s virulence properties were tested in the presence of the molecules, individually as well as in combination. Molecules’ cytotoxicity was tested using human tonsil epithelial cells. The synergistic effects of the molecules on the expression of biofilm and quorum sensing genes were tested using quantitative real-time polymerase chain reaction (qRT-PCR). The molecules were also tested for their impact on LuxS protein by molecular docking, modeling, and free-energy calculations. When the two molecules were assessed in combination (synergistic effect, FIC Index of 0.5), a stronger growth inhibitory activity was exhibited than the individual molecules. The cell surface hydrophobicity, as well as genes involved in quorum sensing and biofilm formation, showed greater suppression when the molecules were tested in combination. The in silico findings also suggest the inhibitory potential of the two molecules against LuxS protein. The binding orientation and the binding affinity of citral and phloretin well support the notion that there is a synergistic effect of citral and phloretin. The data reveal the combination of citral and phloretin as a potent antibacterial agent to combat the virulence of S. pyogenes.